Tackling Africa's chronic disease burden: from the local to the global - Campbell Catherine; Allotey Pascale; Agyemang Charles; Unwin Nigel; de-Graft Aikins Ama; Arhinful Daniel (BMC, 2010)
Abstract Africa faces a double burden of infectious and chronic diseases. While infectious diseases still account for at least 69% of deaths on the continent, age specific mortality rates from chronic diseases as a whole are actually higher in sub Saharan Africa than in virtually all other regions of the world, in both men and women. Over the next ten years the continent is projected to experience the largest increase in death rates from cardiovascular disease, cancer, respiratory disease and diabetes. African health systems are weak and national investments in healthcare training and service delivery continue to prioritise infectious and parasitic diseases. There is a strong consensus that Africa faces significant challenges in chronic disease research, practice and policy. This editorial reviews eight original papers submitted to a Globalization and Health special issue themed: "Africa's chronic disease burden: local and global perspectives". The papers offer new empirical evidence and comprehensive reviews on diabetes in Tanzania, sickle cell disease in Nigeria, chronic mental illness in rural Ghana, HIV/AIDS care-giving among children in Kenya and chronic disease interventions in Ghana and Cameroon. Regional and international reviews are offered on cardiovascular risk in Africa, comorbidity between infectious and chronic diseases and cardiovascular disease, diabetes and established risk factors among populations of sub-Saharan African descent in Europe. We discuss insights from these papers within the contexts of medical, psychological, community and policy dimensions of chronic disease. There is an urgent need for primary and secondary interventions and for African health policymakers and governments to prioritise the development and implementation of chronic disease policies. Two gaps need critical attention. The first gap concerns the need for multidisciplinary models of research to properly inform the design of interventions. The second gap concerns understanding the processes and political economies of policy making in sub Saharan Africa. The economic impact of chronic diseases for families, health systems and governments and the relationships between national policy making and international economic and political pressures have a huge impact on the risk of chronic diseases and the ability of countries to respond to them.